Matrixes and their Applications in Electrical Circuits - Kaltoum Mohammed Meelad Aburaas; Manal Abdulkarim ljlaytah (African Journal of Advanced Pure and Applied Sciences, 2023)
In this paper, we defined the matrix as an important mathematical tool that has a prominent role in various applications. In order to be able to use matrices, we defined algebraic operations on it, mentioned its most important properties and some types, and showed the importance of matrices for mathematical and physical sciences, which lies in the fact that it allows facilitating calculations in various fields. It also helps in studying physical phenomena. The paper aims to study matrices and their applications in electrical circuits. Their use is very useful in solving electrical circuits because matrices are a way to deal with equations with more than one variable and give a good way to solve them. It helps us a lot to find demands in the electrical circuit, such as calculating and knowing the current in force, knowing the voltage, or another physical variable of the electrical circuit, by converting these circuits into equations and then into matrices, and using the inverse of the matrix to solve them for the purpose of facilitating calculations, avoiding errors, and obtaining results in the least possible time. And by using the methods of analysis of the electric circuit, we reached linear equations in the form of different currents and voltages, and we were able to solve these equations to find the value of the variables, were they efforts or currents that enable us to solve the entire electrical circuit, as matrices were a greatly useful aid when dealing with different electrical circuits.